“Making our voices count”: patient action groups as a strategy to engage people with lived experience in implementation of an intervention for hypertensive disorders of pregnancy - Hodges, Jasmine; Fatima, Hiba; McHugh, Kelly; Medearis Costello, Jennifer; Barnett, Kamara; Farahi, Narges; Greene-Jones, Jessica; Jones, Darci; Ledford, Alasia; Lewis, Leila D.; Lopez, Jenniqua; Smith-Janey, Shelby; et al. (Frontiers in Health Services, 2025)
Community-based clinics are a crucial site for the detection and response to Hypertensive Disorders of Pregnancy (HDP), yet many sites lack a standard protocol to address hypertensive emergencies. Moreover, interventions to address this disparity lack a patient centered lens that inform implementation in a community setting. To address these gaps, the Advancing Community and Clinical Care for Childbirth-related Hypertension: Implementation, Engagement and Valuing Equity (ACHIEVE) study is engaging patients with lived experience of HDP. The study integrates community engagement and implementation science to inform adaptation of a hypertension bundle in outpatient clinics. We have created two Patient Action Groups (PAGs) involving members from populations impacted by HDP to guide our community-academic-clinic-coalition team's iterative processes for bundle implementation and resource development. One PAG is comprised of Black and the other Latina/e birthing people, all of whom have lived experience with HDP. Both PAGs meet monthly, led by a racially/ethnically, culturally, or linguistically congruent facilitator. Agendas are co-created, and activities structured to build relationships, trust, and capacity. PAGs review ACHIEVE strategies and materials to spur recommendations and improve respectful care. To facilitate reciprocal exchange, PAG facilitators meet with the ACHIEVE community engagement team and share updates at monthly partner coalition meetings. We recommend PAGs as a power-shifting strategy to ensure those most affected by inequitable perinatal outcomes can engage in research in a way they feel safe, respected and heard. Researchers can also increase trustworthiness by listening and translating patient-generated ideas into strategies that improve clinical care.